IMPLEMENTATION OF LAND DISPUTE HANDLING POLICY - Wibowo, Budi (Jurnal Ilmiah Administrasi Publik, 2013)
Abstract: Implementation Of Land Dispute Handling Policy At Land Office Of Gorontalo Municipality. This study is designed to describe and analyze the implementation of land dispute handling policy at Land Office of Gorontalo municipality. The Land Office has implemented the policy based on new regulation in land dispute handling, but the number of unresolved land dispute was still high. Research method of this study is qualitative method and focusing on the settlement of land disputes in 2011 at Land Office of Gorontalo municipality. The research shows that even though the Land Office has implemented a new regulation, the land office was unable to get optimal result due to some factors such as communication among stakeholders, the attitude of the implementer, the adequacy of the resources and bureaucratic structure. The implementation of the policy has fulfilled some criteria of good governance but failed in some critical points such as responsiveness and participation as well as efficiency in out of court settlement .   Keywords: Land Dispute, Policy Implementation, Good Governance Abstrak :           Pelaksanaan Kebijakan Penanganan Sengketa Tanah di Kantor Pertanahan Kota Gorontalo. Penelitian ini dirancang untuk mendeskripsikan dan menganalisis implementasi kebijakan penanganan sengketa pertanahan di Kantor Pertanahan Kota Gorontalo. Meskipun Kantor Pertanahan telah menerapkan kebijakan berdasarkan peraturan baru dalam penanganan sengketa pertanahan, jumlah sengketa yang belum terselesaikan masih saja tinggi. Penelitian ini menggunakan metode kualitatif dan fokus pada penyelesaian sengketa pertanahan di Kantor Pertanahan.Kota.Gorontalo tahun 2011. Hasil penelitian menunjukkan bahwa meskipun Kantor Pertanahan telah menerapkan peraturan baru, kantor pertanahan tidak bisa mendapatkan hasil yang optimal karena beberapa faktor seperti komunikasi antara para pemangku kepentingan, sikap pelaksana, kecukupan sumber daya dan struktur birokrasi. Implementasi kebijakan telah memenuhi beberapa kriteria good governance tetapi gagal dalam beberapa poin penting seperti respon dan partisipasi serta efisiensi dalam penyelesaian sengketa di luar pengadilan. Kata Kunci : Sengketa Tanah, Implementasi Kebijakan, Good Governance